Optimization of SUAV’s propeller in a hover - Hnidka Jakub; Rozehnal Dalibor; Maňas Karel (MATEC Web of Conferences, 2020)
Small unmanned aerial vehicles (SUAVs) have found a widespread application in past decades. However, as the criticality of the missions for which they can be used increases, the demand for improvement of their efficiency increases as well. The paper focuses on a propeller driven SUAVs of a multirotor type, equipped with an electric motor, battery and propeller. The paper presents a simplified method of calculation of the SUAV maximal endurance, if the characteristics of all components of the propulsion system are known. To improve the overall efficiency of the propulsion system of an SUAV, the correct combination of all propulsion system components is critical. However, the largest impact on the maximal endurance is, arguably, caused by the propeller. The paper proposes a simple method of optimizing the propeller characteristics for hover and compares the proposed propeller design with conventional and commercially available propellers.